2016
DOI: 10.1097/01.prs.0000479933.75887.82
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Combined with General Anesthesia versus General Anesthesia Alone in Patients Undergoing Free Flap Breast Reconstruction

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The role of epidural anesthesia in DIEP free flap breast reconstruction remains unclear. Lou et al 19 demonstrated that epidural anesthesia improved postoperative pain, nausea/vomiting, and decreased opioid consumption without increasing the risk of flap thrombosis. Furthermore, other authors argue that epidural blocks induce vasodilation and therefore improve flap perfusion and oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…The role of epidural anesthesia in DIEP free flap breast reconstruction remains unclear. Lou et al 19 demonstrated that epidural anesthesia improved postoperative pain, nausea/vomiting, and decreased opioid consumption without increasing the risk of flap thrombosis. Furthermore, other authors argue that epidural blocks induce vasodilation and therefore improve flap perfusion and oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…The well-known methods for anesthesia or analgesia objective in breast cancer surgery are TEB, TPVB, and INCB, etc. [ 3 4 5 ]. Compared to conventional regional anesthesia, Pecs block is a less invasive procedure with easier techniques and lesser risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Pain following open-heart surgery could be debilitating, leading to unwanted outcomes such as pulmonary complications [14]. In most study cases, TEA with GA relates to better post-surgery analgesia and lower risks of post-operative respiratory system complications, moreover it helps lowering inflammation [15,16]. Controversially, other study findings states that the addition of epidural anaesthesia to GA doesn't show any less risk in developing major medical complications or mortality rates in long-term and both anaesthesia methods are appropriate [17,18].…”
Section: Discussionmentioning
confidence: 99%